Signalling Theory and Equilibrium in Strategic Management Research: An Assessment and a Research Agenda - Bergh, Donald D.; Connelly, Brian L.; Ketchen, David J.; Shannon, Lu M. (Journal of Management Studies, 2014)
AbstractActors within organizations commonly must make choices armed with incomplete and asymmetrically distributed information. Signalling theory seeks to explain how individuals are able to do so. This theory's primary predictive mechanism is ‘separating equilibrium’, which occurs when a signal's expectations are confirmed through experience. A content analysis finds that most strategic management signalling theory studies have not fully leveraged separating equilibrium. This presents two possible paths for future research. First, some researchers may wish to incorporate separating equilibrium. We illustrate how doing so can uncover new relationships, generate novel insights, and fortify the theory's application. Others who want to theorize about signals, but not examine separating equilibrium, could integrate ideas from signalling theory with other information perspectives. Here a signal becomes one stimulus among many that corporate actors interpret and act upon. We provide research agendas so strategy scholars can apply signalling theory most effectively to meet their research objectives.